BIOLOGICAL CONTROL BY (COCCINELLA ALGERICA, KOVAR 1977) AGAINST THE PUCERON OF CROPS UNDER GREENHOUSES (STATION BIORESSOURCES OF EL OUTAYA CRSTRA) BISKRA; ALGERIA - (:unkn) unknown (University of Eloued جامعة الوادي, 2017)
Inputs from chemicals, particularly pesticides, to control crop pests have adverse effects on soil and the environment, among others. To reduce pest attacks, biological control with indigenous predators is the alternative and the cleanest, most environmentally friendly and ecologically balanced way. In order to achieve this objective, we carried out ladybird breeding and releases were carried out on vegetable crops under glass in the Bioressources (CRSTRA) station where chemical inputs are not used. Â This study shows that massive and successive releases larvae Coccinella algerica stage L3 and L4 (10 to 20 larvae C.algerica Â and Â»350 individuals in Individuals in adult stage / infested plants) Â reduced effectively the population of aphids.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Biological control; Coccinella algerica; Vegetable crops; Station Bioressources